2019
DOI: 10.1007/s42452-019-1227-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nano filler concentration on leakage current and partial discharge properties of zepoxy nano composites

Abstract: Electrical insulation materials play a key role in stable and uninterrupted operation of electrical power system. Researchers working in the field of electrical insulation have turned their focus to nano composite insulation materials for better performance and reliability. A typical nano composite insulation material is a combination of nano particles and base materials. Since last 25 years silicon rubber and epoxy are two widely used electrical insulation materials for outdoor and indoor applications respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…As reported by many researchers previously, this study also indicated that every NP has an optimum concentration threshold at which it gives maximum benefit. This percentage is usually below 1 percent by weight in the for many kinds of base material [20][21][22]26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported by many researchers previously, this study also indicated that every NP has an optimum concentration threshold at which it gives maximum benefit. This percentage is usually below 1 percent by weight in the for many kinds of base material [20][21][22]26].…”
Section: Resultsmentioning
confidence: 99%
“…Further investigation was done in [21] and showed that at 0.6% of TiO 2 @SiO 2 particles in epoxy gives best results. In another study [22] the optimal filler loading of SiO 2 , TiO 2 and TiO 2 @SiO 2 nano-fillers in zepoxy for achieving minimum values of partial discharge and leakage current was investigated. TiO 2 @SiO 2 has shown better performance in epoxy when compared to any other nano filler mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…This cloud will act as an electrostatic barrier, and with the assist of the other scattered traps, they will counter the carrier's mobility, hence improving the volume resistivity. Oppositely, at excessive filler contents, agglomeration probabilities increased and trapping energy minimized; consequently, the conductance improves and the resistivity decreases [17], [18].…”
Section: Volume Resistivitymentioning
confidence: 99%
“…The interaction of the fillers and polymers has an impact on the chemical and physical properties. [ 28–30 ]…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of the fillers and polymers has an impact on the chemical and physical properties. [28][29][30] During long-distance power transmission, the electronic circuits involved stress the cable insulation significantly. Therefore, to employ environment-friendly dielectric materials, materials such as RCP needs to be explored.…”
Section: Introductionmentioning
confidence: 99%